Uji Aktivitas Fraksi Etil Asetat Daun Daruju (Acanthus Ilicifolius L) terhadap Bakteri Propionibacterium Acnes dan Staphylococcus Epidermidis - Rabima Rabima; Riris Arisma Sunyaluri (Jurnal Health Sains, 2021)
Daruju leaves (Acanthus Ilicifolius L) is a type of plant that is widely grown and developed in Indonesia. Daruju leaves (Acanthus Ilicifolius L) found the presence of many secondary metabolite compounds. Secondary metabolite compounds are non polar, semipolar and polar so that to maximize the extraction of secondary metabolites, fractionation is carried out. The fractionation process in this study used n-hexane, ethyl acetate and methanol as solvent, while the test bacteria used were Propionibacterium acnes and Staphylococcus epidermidis. Antibacterial activity testing was carried out using the agar diffusion method. The antibacterial activity test showed that the ethyl aceat fraction of Daruju leaves (Acanthus Ilicifolius L) was able to inhibit the growth of Propionibacterium acnes and Staphylococcus epidermidis bacteria. The activity test of the ethyl acetate fraction of Daruju leaves (Acanthus Ilicifolius L) on Propionibacterium acnes bacteria was obtained at a concentration of 20% with an average diameter of the inhibition zone of 20.99 mm where the inhibition zone category was included in the strong category, while the Stаphylococcus epidermidis bacteria were obtained in concentration of 15% with an average diameter of the inhibition zone of 20.21 mm where the inhibition zone category is included in the strong category.